EDUCAÇÃO EM SAÚDE: CONTROLANDO A PEDICULOSE EM CRIANÇAS DO ENSINO FUNDAMENTAL - SOUZA MARTINS, LORRANE ISABELLE; DE OLIVEIRA ALCANTARA, KELLY CRISTINA; RODRIGUES CAMPOS, NATHÁLIA JAQUELINE; SANTOS DE JESUS, THAINÁ; MENDES FERREIRA, YARA (Sinapse Múltipla, 2019)